Análise de séries meteorológicas de altitude na grande Cuiabá com métodos da teoria da complexidade - Vidal, Lúcio Ângelo (2012)
The objective of this study was to characterize the meteorological variables of altitude temperature, relative humidity, dew point, wind, geopotential height and entropy for unit mass of air in Cuiabá, to study the periodicities of these series taking advantage of the method of Fourier and find the value of the correlation dimension in the isobaric surfaces 850, 700, 500, 300 and 200 hPa of atmospheric soundings obtained DTCEA-CY performed in the period October 1, 2004 to December 31, 2010. Periodicities obtained were of 397.5 days and 198.8 days with the Fourier series. The dimension of correlation values obtained are mostly not intact, in the other words, the series have a strange attractor and has a value greater than 2, which indicates that the variables are non-periodic oscillation and an inherent unpredictability. You can see that the correlation dimension decreases with altitude in varying wind and relative humidity. The extent of immersion in the variables obtained in the various analyzed levels varied between 8 and 10.